2007
DOI: 10.1111/j.1553-2712.2007.tb01813.x
|View full text |Cite
|
Sign up to set email alerts
|

Failed Validation of the Argall Weight Formula for Estimating Children's Weight in an Australian Emergency Department

Abstract: Background: An estimate of a child's weight is required for critical interventions, particularly pharmacotherapy. Weight measurement is not always practical, so weight estimation methods are used. Recently, a new weight estimation formula was suggested. The Argall formula estimates weight in kilograms as follows: (age in years + 2) Â 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The Broselow r value is similar to our study, but the APLS value is inconsistent with our results. Nguyen et al 14 showed that Argall's modification formula had poor accuracy in children, especially >35 kg. Our results also showed that it had one of the lowest correlations in the 0-5 years age group (adjusted R-squared 0.6548).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Broselow r value is similar to our study, but the APLS value is inconsistent with our results. Nguyen et al 14 showed that Argall's modification formula had poor accuracy in children, especially >35 kg. Our results also showed that it had one of the lowest correlations in the 0-5 years age group (adjusted R-squared 0.6548).…”
Section: Discussionmentioning
confidence: 99%
“…Using their data, they suggested the 'Argall's modification' formula; this has also failed in its validation when tested on Australian children. 14 More recently, there has again been the concern that these formulas could be underestimating the weight of children as a trend towards increasing height, mass and obesity is being seen in the developed world. 15 This has led to studies devising new age-based formulas/charts; the 'best guess' formula in Australia, 16 Luscombe and Owens 17 in the UK and in New Zealand with the large-for-age Pacific Island and Maori children.…”
Section: Introductionmentioning
confidence: 99%
“…This was a secondary analysis of a prospective, observational study that has been previously reported. 8 We studied a convenience sample of paediatric patients who presented to the ED of a metropolitan community teaching hospital with a paediatric ED census of 23 000 annually. We collected data on stable children, aged between 1 and 11 years, with a wide variety of clinical conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The contemporary methods have frequently been shown to lack acceptable accuracy and consistency of performance in different populations. 1,[5][6][7][8][9] Even the Broselow tape, which is arguably the gold-standard weight-estimation system, has been shown to perform poorly in a number of studies in the last decade. 10,11,4,12 The poor performance of these systems is principally because of the wide variability of body habitus that is not accounted for in these weight-estimation systems.…”
Section: What Is the Problem With Current Weight-estimation Systems?mentioning
confidence: 99%